New onset diabetes after transplantation in renal transplant recipients at Tygerberg Hospital - Bapoo, Nabeel A; Nel, Johan D (African Journal of Nephrology, 2014)
<p style="margin: 4px; color: #000000; font-family: 'Merrieweather sans', sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">New Onset Diabetes after Transplantation (NODAT) is a common complication of renal transplantation worldwide.However, there is very little data available regarding this condition in Sub-Saharan Africa. This study was thereforeconducted in order to determine the incidence of NODAT and its associated risk factors in a South African renaltransplant population. A retrospective analysis was conducted on 221 patients who underwent renal transplants atTygerberg Hospital during the period January 1st 1995 to December 31st 2008. <p style="margin: 4px; color: #000000; font-family: 'Merrieweather sans', sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">Specific information was retrieved from patient files in order to determine the study outcomes. Fifty of the 221 patientswere found to have NODAT reflecting an incidence of 22.6% (95% CI 0.17-0.28). The cumulative incidences of NODATat three, 12 and 36 months were 9%, 12% and 17% respectively. The mean time to onset of NODAT was 18 monthsafter transplantation (95% CI 11.3-25.3) and the mean age at diagnoses of NODAT was 41 years (95% CI 38.9-44.8).Transplantation at the age of 40 years (odds ratio = 1.05) as well the usage of tacrolimus (odds ratio = 0.43) was foundto increase the risk of developing NODAT. The development of NODAT did not have any effect on graft or patientsurvival in this study. <p style="margin: 4px; color: #000000; font-family: 'Merrieweather sans', sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">The incidence of NODAT in a South African population appears to be as high as it is worldwide with the first year posttransplantationcarrying the greatest risk for its development. The risk for development of NODAT is increased as thetime post-transplantation increases. Transplantation from the age of 40 years and the use of tacrolimus appear to be themost significant risk factors.